2009
DOI: 10.1371/journal.pone.0007859
|View full text |Cite
|
Sign up to set email alerts
|

New Mouse Lines for the Analysis of Neuronal Morphology Using CreER(T)/loxP-Directed Sparse Labeling

Abstract: BackgroundPharmacologic control of Cre-mediated recombination using tamoxifen-dependent activation of a Cre-estrogen receptor ligand binding domain fusion protein [CreER(T)] is widely used to modify and/or visualize cells in the mouse.Methods and FindingsWe describe here two new mouse lines, constructed by gene targeting to the Rosa26 locus to facilitate Cre-mediated cell modification. These lines should prove particularly useful in the context of sparse labeling experiments. The R26rtTACreER line provides ubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 50 publications
4
91
0
Order By: Relevance
“…As shown in Fig. 1E, we developed three distinct animal models for the studies reported here by breeding these E3= F/F Ed Ϫ/Ϫ mice with either germ line-expressing Cre mice (28) or with tamoxifen-inducible Cre mice (22) or with mice specifically expressing Cre in mature B cells (23). Successful deletion of E3= in each of these cases generates E3=…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Fig. 1E, we developed three distinct animal models for the studies reported here by breeding these E3= F/F Ed Ϫ/Ϫ mice with either germ line-expressing Cre mice (28) or with tamoxifen-inducible Cre mice (22) or with mice specifically expressing Cre in mature B cells (23). Successful deletion of E3= in each of these cases generates E3=…”
Section: Resultsmentioning
confidence: 99%
“…As our initial approach to test for the importance of the Ig gene's downstream enhancers on continued gene expression following their deletion, we bred E3= F/F Ed Ϫ/Ϫ mice with those harboring a tamoxifen-inducible Cre [ROSA26CreER(T) (22)] to obtain a homozygous E3= F/F Ed Ϫ/Ϫ ROSA26CreER(T) line. It is known that the lifetime of splenic mature B cells can be from several weeks to months (29), so we sought to delete E3= in such nonreplicating mature B cells for the subsequent analysis of Ig gene expression in these cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 1 compares the brain defects in Fz3 −/− mice visualized by NF immunostaining with the trajectories of dorsal thalamic axons visualized with a RORα-IRES-Cre knock-in allele and a Cre-controlled human placental alkaline phosphatase (hPLAP; hereafter "AP") reporter, R26iAP (10,11). In the prenatal mouse brain, RORα is expressed in the dorsal thalamus (12).…”
Section: Significancementioning
confidence: 99%
“…This project further asks for lineage data at several intermediate stages of retinogenesis, and these results will be best compared to adult clone composition in the context of a unique and consistent mouse line. There are currently other mouse lines available to achieve sparse Cremediated recombination in the retina (Badea et al, 2009b;Yun et al, 2009;Brzezinski et al, 2011). In these lines, a drug such as tamoxifen is used to activate Cre recombinase activity at a specific time, and limiting dilutions can be applied to restrict recombination to a subset of RPCs.…”
Section: Cre Recombination In Rpcsmentioning
confidence: 99%